Climate change and violent Conflict in transboundary water: Lake chad case study - Nkom, Nton Bola (2020)
The issue of climate change and conflict is causing controversy globally. Although comparative research on climate change is rapidly increasing, significant gaps in knowledge still exists as far as its relationship with conflict is concerned. Many existing studies provide mostly inconclusive insights, with contradictory or weak demonstrated effects of climate variability and change on violent conflict. This article reviews the empirical relationship between climate change conflicts. Making an enormous analysis of the causality pathways of Climate change and conflict, using the Case study that falls under the most climate-vulnerable regions - Lake Chad Basin. From the analysis -the fact remains that climate ch ange does not cause conflict directly, but cause conflict indirectly, this is confirmed through the three stages of the causal pathways analysis of the Lake Chad case study.